Change of Extracellular Glutamate Level in Striatum during Deep Brain Stimulation of the Entopeduncular Nucleus in Rats - Lee, Hyun-ju (J Korean Neurosurg Soc, 2019)
OBJECTIVE: Globus pallidus interna (GPi) is acknowledged as an essential treatment for advanced Parkinson’s disease (PD). Nonetheless, the neurotransmitter study about its results is undiscovered. The goal of this research was to examine influences of entopeduncular nucleus (EPN) stimulation, identical to human GPi, in no-lesioned (NL) rat and 6-hydroxydopamine (6-HD)-lesioned rat on glutamate change in the striatum. METHODS: Extracellular glutamate level changes in striatum of NL category, NL with deep brain stimulation (DBS) category, 6-HD category, and 6-HD with DBS category were examined using microdialysis and high-pressure liquid chromatography. Tyrosine hydroxylase (TH) immunoreactivities in substantia nigra and striatum of the four categories were also analyzed. RESULTS: Extracellular glutamate levels in the striatum of NL with DBS category and 6-HD with DBS category were significantly increased by EPN stimulation compared to those in the NL category and 6-HD category. EPN stimulation had no significant effect on the expression of TH in NL or 6-HD category. CONCLUSION: Clinical results of GPi DBS are not only limited to direct inhibitory outflow to thalamus. They also include extensive alteration within basal ganglia.